Nano-dimensional properties of Si-FinFET transistor based on ION/IOFF ratio and subthreshold swing (SS) - Mahmood, Ahmed; Hashim, Yasir; Hadi, Manap (JACS, 2018)
This paper presents design the optimal channel dimensions for Silicon Fin Feld Effect Transistor (SiFinFET) for improvement electrical characteristic of Si-FinFET depending on the electrical characteristics of the channel (ION/IOFF, SS, VT, DIBL). The MuGFET simulation tool has been using to investigate the electrical characteristics of Si FinFET. The current voltage characteristics has been simulating with different dimensions channel (length, width and oxide thickness). The best channel dimensions of Si-FinFET observed based on electrical characteristics at the working voltage VDD range of 0-5 V. Note that the results with the scaling channel dimensions. Depending on ION/IOFF ratio higher value, and nearest SS to the ideal SS, the best scaling channel dimensions (K) will be K=0.25 at VDD=5 V and K=0.25 at VDD=0.5 V.